Higher risk of respiratory infections and otitis media in cleft lip and/or palate patients: the Japan Environment and Children's Study - Hiroshi Kurosaka; Takashi Kimura; Jia-Yi Dong; Meishan Cui; Satoyo Ikehara; Kimiko Ueda; Hiroyasu Iso; Takashi Yamashiro; the Japan Environment and Children's Study Group (Komiyama Printing Co. Ltd, 2024)
Background: Cleft lip and/or palate (CL/P) is one of the most frequent craniofacial disorder which could associate with a wide range of craniofacial complication. In order to perform comprehensive care of CL/P patients, it is crucial to elucidate the link of CL/P and general clinical conditions. This study aims to elucidate the relationships between medical history of different CL/P types and infectious diseases to serve as a reference for the comprehensive care of patients with CL/P. Methods: We investigated the association between a history different types of CL/P and the risk of infectious diseases among 1-year old children in the Japan Environment and Children's Study (JECS). Among the 104,065 registered fetal records, 92,590 eligible participants were included in the analysis. Results: The multivariable-adjusted risk ratios (95% confidence intervals) for otitis media were increased in cleft lip and palate (CLP) and cleft palate only (CPO) groups by 3.81 (2.73-5.31) and 2.27 (1.22-4.22), respectively. The prevalence of Upper respiratory inflammation (URTI) was not associated with CLP, cleft lip only, or CPO. However, analysis in all groups showed a higher risk of URTI compared with the control group (1.31 [1.04-1.66]). Conclusions: CL/P care requires additional attention to prevent airway infectious diseases such as URTI before 1 year of age. Further research is warranted to elucidate the relationship between CL/P and general medical conditions.